KAMPUNG SIAGA (Studi Penanganan Covid-19 Berbasis Masyarakat Melalui Program Kampung Siaga Candi Hebat di Kota Semarang 2020-2022) - Ariyanti, Ellyana -; Adnan, Muhammad -; -, Fitriyah - (Journal of Politic and Government Studies, 2024)
The very high spread of Covid-19 in Semarang City has prompted the Semarang City Government together with the Semarang City Police to initiate the Kampung Siaga Candi Hebat program to prevent the spread of Covid-19 in the Semarang City area and to increase the community's sense of mutual cooperation. The Kampung Siaga Candi Hebat is carried out on a community basis which emphasizes empowering the potential of the people in the environment. This research was conducted to determine the implementation and describe community-based handling of Covid-19 through the Kampung Siaga Candi Hebat in Semarang City in 2020-2022 and to identify what activities were carried out in the program. This research adopts Keith Davis's theory of community participation, Edmonson's citizenship theory, and Mitchell's social cohesion theory. This research uses descriptive qualitative research and uses interactive research strategies such as in-depth interviews, documents, and complementary techniques such as photos to find out the implementation of community-based handling of Covid-19 through the Kampung Siaga Candi Hebat program in Semarang City. The research results show that the implementation of handling Covid-19 is community-based using 5 indicators, namely health alert, socio-economic, logistics, security, and communication & creativity. Apart from these five indicators, community-based handling of Covid-19 also creates a society that is participatory, cohesive, and has awareness and independence in fighting the pandemic